Auteur collectif ou exégète singulier ? Abélard et la Bible - Cédric Giraud (Artes)
The paper analyzes the importance of Peter Abelard in twelfth-century biblical exegesis. Abelard distinguished himself as an innovative young teacher when he decided to explain the book of Ezekiel independently, rather than following the traditional approach of his master Anselm of Laon. Although his commentary on Ezekiel has been lost, his other exegetical works, such as sermons, commentaries on the Hexameron and Epistle to the Romans, and Problemata Heloissae, demonstrate his significant contribution to exegesis. Historical criticism has underestimated Abelard’s role as an exegete, however, focusing more on his correspondence and theologies. This study proposes to reevaluate Problemata Heloissae in light of how Abelard addresses the exegetical questions posed by Heloise: he employs a method combining tradition and originality, thereby showing that his exegesis is both collective and singular.